2021
DOI: 10.1108/josm-11-2020-0429
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of business model innovation for advancing IoT platforms

Abstract: PurposeThe emergence of Internet of Things (IoT) platforms in product companies opens up new data-driven business opportunities. This paper looks at the emergence of these IoT platforms from a business-model perspective.Design/methodology/approachThe study applies a mixed method with two research studies: Study I–a cluster analysis based on a quantitative survey, and Study II–case studies based on qualitative interviews.FindingsThe findings reveal that there is no gradual shift in a company's business model, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 73 publications
(116 reference statements)
0
14
0
Order By: Relevance
“…Martens et al (2022) identified eight challenges to IoT (administration, data collection and management, cost innovation, integration, efficiency matrix, people, security, bringing value, and business solution) while Aamer et al (2021) suggested that IoT challenges fit into five thematic challenges (technical, financial, social, operational, educational and governmental). The challenges inherent in current IoT systems are likely to be key to the variable commercial success of IoT adoption that was identified by Markfort et al (2022).…”
Section: Challenges and Factors Affecting Iot Implementationmentioning
confidence: 99%
See 3 more Smart Citations
“…Martens et al (2022) identified eight challenges to IoT (administration, data collection and management, cost innovation, integration, efficiency matrix, people, security, bringing value, and business solution) while Aamer et al (2021) suggested that IoT challenges fit into five thematic challenges (technical, financial, social, operational, educational and governmental). The challenges inherent in current IoT systems are likely to be key to the variable commercial success of IoT adoption that was identified by Markfort et al (2022).…”
Section: Challenges and Factors Affecting Iot Implementationmentioning
confidence: 99%
“…(2021) suggested that IoT challenges fit into five thematic challenges (technical, financial, social, operational, educational and governmental). The challenges inherent in current IoT systems are likely to be key to the variable commercial success of IoT adoption that was identified by Markfort et al. (2022).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Both trends impact on each other, thereby generating new business opportunities and disruption in markets (Frank et al, 2019;Kolagar et al, 2021). The latest digital technologies, such as the Internet of things (IoT), cloud computing and artificial intelligence (AI), enable companies to provide more and better value for customers through smart products and advanced services (Ardolino et al, 2018;Vendrell-Herrero et al, 2021a, b), often enabled by digital platforms (Cusumano, 2022;Markfort et al, 2021). Digital service innovation (DSI) combines both digital and service innovation logics, leading to digital servitization and other innovative, digitally enabled business models (Opazo-Bas aez et al, 2021;Raddats et al, 2019;Vendrell-Herrero et al, 2023).…”
Section: Introductionmentioning
confidence: 99%